PENERAPAN TEKNIK SCAFFOLDING SEBAGAI UPAYA MENINGKATKAN KEMANDIRIAN BELAJAR ANAK USIA 5-6 TAHUN DI TK KRISTEN KADASITURU TERPADU - Suprihatin, Eny; Rosita, Desti (EDULEAD: Journal of Christian Education and Leadership, 2020)
Independence is the attitude of life needed for the progress of a nation. An independent human being is able to mature to face the challenges of the times. Independence cannot happen instantly, it needs to be familiarized. The right time for habituation is early age. Research on the application of Scaffolding learning techniques as an effort to increase the learning independence of children aged 5-6 years, using the Classroom Action Research methodology conducted at Kadasituru Integrated Christian Kindergarten. The research model used is the Kurt Lewin model. Four stages are carried out: planning, implementing, observing and reflecting. The result is a significant increase in the improvement of children's learning independence. Initial observation of the level of independence of 17 research subjects the average score was 6.61% in the category of Not Developing (BB). After taking action in four cycles, children's learning independence significantly increased the average score of 98.52% to meet the criteria of Very Good Development (BSB).